Knowledge and Attitude Toward Lumbar Puncture Among Medina Population - Asma Alshanqiti (Journal of Spine Practice)
Introduction: Lumbar puncture (LP) is one of the invasive procedures performed to obtain information about cerebrospinal fluid. It has diagnostic and therapeutic purposes for various neurological cases. Previous studies among different populations have indicated that there is a lack of research focusing on individuals’ knowledge and attitude toward LP. Patient who refuse LP may be exposed to unneeded hospital admission, or unnecessary empirical antibiotic treatment. A literature search found a lack of studies regarding LP knowledge and perception among Al-Medina residents. To address that gap, this study aimed at assessing the knowledge and attitude toward LP among the Al-Medina population.